The forgotten origin of Acanthobothrium Blanchard, 1848 (Tetraphyllidea: Onchobothriidae) - Machado, Denis Jacob; de Luna Marques, Fernando Portella (Zootaxa, 2012)
The genus Acanthobothrium assembles a set of cosmopolitan onchobothriid tapeworms parasites of elasmobranchs. Despite its clear diagnostic features, which include a scolex with four bothridia each bearing three loculi and a pair of bipronged hooks, this genus is represented by species that possess a diversity of morphologies and host lineages (e.g. rays, skates, guitarfishes, and sharks; Campbell & Beveridge 2002; Zschoche et al. 2011). The wide distribution of this genus, its diverse morphology, and, perhaps most importantly, its lengthy and complex taxonomic history likely account for the fact that, to date, the absolute number of valid species, of potentially more than 200 nominal species, cannot be assigned to the genus with certainty. Clearly, a taxonomic revision of this group is overdue; a task that certainly will only be accomplished by collaborative efforts of cestodologists around the globe, given the widespread distribution of its species and the necessity of collecting new material to verify host identities and morphology in many cases. It is not our purpose here to provide such a revision. However, in order to get the basis for such a task, it is our intention to clarify the authorship, date of publication, type species, and type host of Acanthobothrium. To the best of our understanding, these have been mistakenly assigned throughout the taxonomic history of the genus.